Integrated Physiotherapeutic Approach in Ischemic Stroke (REMUNOM, 2025)
Stroke is characterized by sudden neurological deficit resulting from vascular injury, classified as ischemic or hemorrhagic, and resulting in motor, sensory, and functional deficits. This study aimed to analyze the physiotherapy evolution of a 73-year-old female patient diagnosed with ischemic stroke, treated at the Physiotherapy Teaching and Research Clinic of Iguaçu University (UNIG). This is a case study, conducted through detailed evaluation including anamnesis, specific physical examinations, joint tests, muscle strength, perimetry, measurement, sensitivity, and reflexes. The therapeutic plan was structured with functional electrical stimulation (FES), therapeutic stretching, seated training, ergometer bicycle, and muscle strengthening. After fifteen sessions, a significant reduction in pain was observed (VAS from 8 to 5), slight gains in the range of motion of the upper and lower limbs, and partial improvement in functional mobility. Physiotherapeutic rehabilitation demonstrated a positive response, although short-term goals have not yet been fully achieved. The findings show that systematized physiotherapy, including FES, kinesiotherapy, and functional exercises, contributes to the gradual recovery of function, pain reduction, and increased independence in activities of daily living. It is concluded that continuity and individualization of treatment are essential to maximize functional recovery and quality of life for post-stroke patients.